FRI0025 The rheumatoid arthritis patient in the clinic: comparing 1319 consecutive dmard therapies. (1st June 2001) - Aletaha, D; Smolen, JS
Abstract : Background: Objectives: Rheumatoid arthritis (RA) patients are prone to receive a series of consecutive disease modifying antirheumatic drugs (DMARDs). This study was performed to reveal possible strategies and treatment patterns with traditional DMARDs in the 1980s and 1990s to serve as a basis for improvement of treatment strategies. Methods: 593 RA outpatients (80.4% women) from two hospitals who received 1319 consecutive courses of DMARDs (2376 patient years of therapy) were followed from their first presentation throughout the whole course of their disease. Data were collected as dosage, duration of therapy, reason for discontinuation and all adverse effects that had emerged during DMARD treatment. Furthermore, efficacy of individual DMARDs (using CRP and ESR as surrogates) and survival (applying Kaplan-Meier-estimates) of drug therapy were assessed. Results: Chloroquine (CQ), sulfasalazine (SSZ), and gold compounds (OG, PG) were typical first DMARDs, while penicillamine (DPA), methotrexate (MTX), azathioprine (AZP), cyclosporine (CyA), and combinations were usually used later in the disease course. MTX, SSZ and CQ were the most commonly employed DMARDs throughout the years, 1 however, SSZ and CQ therapies were mostly followed by MTX. Disease characteristics did not differ between patients with longstanding therapy and those with therapies terminated early. For consecutive DMARDs, there was a decreasing tendency of efficacy (reduction of acute phase response) and of treatment duration (Table 1 ). Conclusion: MTX is the most commonly employed DMARD therapy for RA and is increasingly used as first therapy in newly diagnosed RA. Patients with high disease activity are more often subjected to MTX therapy than to other DMARDs, while those with low activity were more likely to receive SSZ or CQ. There is a loss of efficacy with increasing number of subsequent therapies. Thus, treatment duration decreases with increasing number of consecutive DMARD therapies. Reference: Felson DT, Anderson JJ, Meenan RF. Use of short-term efficacy/toxicity tradeoffs to select second-line drugs in rheumatoid arthritis. A metaanalysis of published clinical trials. Arthritis Rheum. 1992;35:1117–25